Application of Very Urgent Criteria in The Marriage Dispensation Norms for the Protection of Children: Analysis of Jasser Auda's Theory - Asmuni, Asmuni; Rezha Nur Adikara , Rezha Nur Adikara (Jurnal Hukum Islam, 2024)
The renewal of marriage legal norms regarding the minimum age limit for marriage with the criteria of "very urgent" has given rise to disparities in the judges' consideration when applying decisions on marriage dispensation cases,  at the same time increasing the number of child marriages in the religious courts. This research discusses two main patterns, i.e.: the application of the "very urgent" criteria in marriage dispensation cases in the Religious Courts and; the relevance of " very urgent"  criteria toward protecting women and children. The theory of the maqāṣid syarī'ah system by Jasser Auda was used as an analytical tool from a contemporary jurisprudential perspective. This research uses a normative juridical approach with data collection techniques using library research. The results of the study show that the form of application of Jasser Auda's maqāṣid syarī'ah system theory in understanding the "very urgent" criteria can at least be analyzed from 4 (four) four conditions that may occur in children whom marriage dispensation is requested,i.e: pregnancy in the child, the potential for free sex, the potential for unregistered marriages, as well as the potential for continuity of education for children who apply for marriage dispensation. These conditions are linear with the six features of Jasser Auda's maqāṣid syarī'ah system,i.e.:   the cognitive nature of the system, wholeness, openness, interrelated hierarchy, multi-dimensionality, and focus on goals.  In addition, the "very urgent" criteria norm is linear with the objectives of regulations regarding child protection and the elimination of domestic violence.